Cover Image. Issue 3 (20th January 2020) - Roger, Elise; Pichat, Cedric; Torlay, Laurent; David, Olivier; Renard, Felix; Banjac, Sonja; Attyé, Arnaud; Minotti, Lorella; Lamalle, Laurent; Kahane, Philippe; Baciu, Monica
Abstract : COVER ILLUSTRATION Representation of a resting‐state fMRI map projected on a 3D brain render and on which is affixed/anchored a correlation matrix derived from resting‐state fMRI data, serving as the basis for assessing functional connectivity.